Potential of Vanname Shrimp Skin Astanxanthin Hydrolyzate as Alpha Glucosidase Enzyme Inhibitor - Heriansyah, Ivan; Karnila, Rahman; Buchari, Dewita (Jurnal Perikanan dan Kelautan, 2023)
The purpose of the study was to analyze hydrolysate astaxanthin as an inhibitor of the enzyme alf glucosidase. The method used is an experimental method by applying a Complete Random Design (RAL) The treatment used is a concentration of different papain enzymes, consisting of 3 treatment levels namely t1 (3%), t2 (6%), and t3 (9%). Observations made are 1) proximal analysis; 2) analysis of hydrolysate astaxanthin and its antioxidant activity; 3) analysis of the inhibition test of the enzyme alpha glucosidase and its inhibitory mechanism. The results showed that the proxmat of vanname shrimp skin flour is; water content (9.20% bb), ash (31.46% bk), fat (1.64% bk), protein (37.60% bk), and carbohydrates (29.29% bk) (by different) with a yield of 36.22%. The highest astaxanthin content at the 3% papain enzyme concentration of 3.57 μg/g with the best antioxidant activity has the smallest IC50 value of 88,793 ppm and astaxanthin shows inhibition activity of alpha glucoside enzyme by 49.38% - 58.87% and astaxanthin has a competitive enzyme inhibition mechanism resulting in a decrease in postrandial blood glucose levels.